2014
DOI: 10.3390/ma7064601
|View full text |Cite
|
Sign up to set email alerts
|

From Cellulosic Based Liquid Crystalline Sheared Solutions to 1D and 2D Soft Materials

Abstract: Liquid crystalline cellulosic-based solutions described by distinctive properties are at the origin of different kinds of multifunctional materials with unique characteristics. These solutions can form chiral nematic phases at rest, with tuneable photonic behavior, and exhibit a complex behavior associated with the onset of a network of director field defects under shear. Techniques, such as Nuclear Magnetic Resonance (NMR), Rheology coupled with NMR (Rheo-NMR), rheology, optical methods, Magnetic Resonance Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Building on these studies, we recently demonstrated that organosolv lignin drastically stabilizes the shear-induced oriented structure of hydroxypropyl cellulose, the so-called band texture . The band texture is a well-known phenomenon for LCPs. The bulk macromolecular relaxation of the elastic energy stored in the texture occurs in a sinoidal or zigzag manner and appears as a banded microstructure under crossed polarizers. In our prior study, we revealed that the stability of the band texture was not only drastically increased by the presence of organosolv lignin but further allowed the manufacture of highly anisotropic “banded films” upon drying. In this way, blend films were prepared exhibiting an increase in modulus and tensile strength of up to 500% compared to pure HPC, i.e., values of 2.7 GPa and 60 MPa, respectively, for blend films containing 30% lignin (by weight).…”
Section: Introductionmentioning
confidence: 90%
“…Building on these studies, we recently demonstrated that organosolv lignin drastically stabilizes the shear-induced oriented structure of hydroxypropyl cellulose, the so-called band texture . The band texture is a well-known phenomenon for LCPs. The bulk macromolecular relaxation of the elastic energy stored in the texture occurs in a sinoidal or zigzag manner and appears as a banded microstructure under crossed polarizers. In our prior study, we revealed that the stability of the band texture was not only drastically increased by the presence of organosolv lignin but further allowed the manufacture of highly anisotropic “banded films” upon drying. In this way, blend films were prepared exhibiting an increase in modulus and tensile strength of up to 500% compared to pure HPC, i.e., values of 2.7 GPa and 60 MPa, respectively, for blend films containing 30% lignin (by weight).…”
Section: Introductionmentioning
confidence: 90%
“…The possibility to lock the characteristic shear-induced band texture by chemical cross-linking has also been reported for HPC. Based on the retention of this specific supramolecular arrangement, Godinho and her co-workers ,, drew attention to cellulosic LCPs as potential network materials for soft stimulus-responsive devices. Furthermore, an elastomer-like behavior was observed by Sena et al, who locked the band texture of acetylated HPC by cross-linking with a diisocyanate.…”
Section: Introductionmentioning
confidence: 94%
“…There are various types of defects, in which the spiral (screw) defects are also very common in the process of fabricating microstructures. The characteristics of these defects have been described in refs 43 and 44 . In the following, we discuss how to identify the spiral defects by using these states.…”
Section: Resultsmentioning
confidence: 99%